Pedagogical Foresight Views of The Jadid Enlighteners - Utaev Akram Yuldoshevich (International Journal of Pedagogics, 2026)
In the process of globalization, educating young people as individuals who can oppose harmful influences and trends, and who possess firm confidence and outlook in life, in the spirit of patriotism, civic sense, tolerance, respect for laws, as well as national and universal values, serves as an important source in achieving effectiveness in the education system and plays a key role in the pedagogical heritage. This article analyzes the pedagogical foresight views, content, and mechanisms of the Jadid enlighteners, who are one of the important pedagogical sources, and presents the author's individual approaches.